Case report: A case of hyperthyroidism secondary to bone metastasis of differentiated thyroid cancer - Gu, Tingyu; Zhao, Zhihong; Shi, Yuanyuan; Sun, Zhenhua; Wang, Yao; He, Zhiyuan; Wang, Kun (Frontiers in Oncology, 2024)
It is usually believed that differentiated thyroid cancer is less likely to have distant metastases and rarely occurs secondary to hyperthyroidism. In our case report, we describe a patient diagnosed with thyroid fetal adenoma in 2002 who subsequently presented with a painful lump in her right rib. Through puncture biopsy, the mass was considered as metastatic follicular thyroid carcinoma, and then she appeared to have hyperthyroidism. The results of SPECT examination and other tests suggested that the hyperthyroidism was secondary to the thyroid cancer. The patient further underwent total thyroidectomy, and the pathology did not find any follicular thyroid foci. In this article, we analyze and discuss this case and review the relevant literature.